Motivation and Consumers’ Attitudes Mediate The Effect of Social Media toward Purchase Decisions on Generation Z via Market Place - Widiawati, Kristiana; Wiladiyah, Lala; Winata, Siti Dewi (PT Mattawang Mediatama Solution, 2025)
The aim of this research work is to investigate the impact of motivations and attitudes towards social media on Generation Z purchasing behavior in the marketplace. This research is about what affects people’s purchase and how social media can be used in good ways in order to succeed as a marketer. The research method is a quantitative with analytical tool SMART PLS. The respondents from Generation Z in Jabodetabek as many as 236. The path analysis was used to assess the association of the variables studied. Influence on Purchase Decision The findings from the study reveal that social media has a direct as well as indirect impact on the consumer purchase decision (via consumer motivation and attitude). It can be concluded, from the path coefficient value, that motivation has a very significant effect on to purchasing decision (all hypotheses are accepted).